Seeing and Being Green? The Effect of Money Priming on Willingness to Perform Sustainable Actions, Social Connectedness, and Prosociality. Issue 1 (2nd January 2016) - Capaldi, Colin A.; Zelenski, John M.
ABSTRACT: This investigation attempted to conceptually replicate/extend research that suggests that reminders of money can inhibit prosociality, promote self-sufficiency, and influence political beliefs. Based on these results, we hypothesized that money primes would decrease willingness to engage in sustainable actions. We also predicted that people would distribute points less prosocially and feel less socially connected when money was primed. Individuals were recruited from an undergraduate participant pool and MTurk. Meta-analytic results across the two samples revealed that money priming did not have a significant impact on willingness to act sustainably, but it did cause participants to distribute points less prosocially and report lower social connectedness than individuals in the control condition. While effects were smaller than those reported in Vohs, Mead, and Goode (2006), this study still offers support for the detrimental impact of reminders of money on interpersonal relations.